Dos modelos classificatórios tradicionais na ciência da informação à folksonomia: um enfoque discursivo - Reis, Lívia de Lima (2012)
This research is about the models of organization and classification of information in the field of Librarianship and Information Science, prioritizing a more dialogical form of organization of information, the folksonomy. Initially, we aim to understand, through the archaeological and genealogical Foucault s methods, the conditions of possibility of two different classification procedures, one traditional and other contemporary. For doing this, a contextualization of the field of knowledge called Librarianship and Information Science will be presented, as well as the models of information organization used, and this field s tendencies. In sequence, considering the theoretical categories derived from the works of Bakhtin and Foucault, we will analyze different forms of classification of knowledge and of language concepts that underlie them. Some of the results indicate that there is a new form of power implied in the social practice of folksonomy, understood as one collaborative tool to organize the information in the Web 2.0, in which the subjects themselves act in the regulation of discourse and in the creation of new concepts. The analytical reflections illustrate that the subjects act in a responsive way on the internet by manipulating linguistic features through the creation of tags related to different semantic universes. We also intended to locate points of resistance focusing on the linguistic and discursive practices of folksonomy as a locus of social change. The Web 2.0 works based on a dynamics of incitement and pleasure which reinforces the flow of information and online relationships, thus, folksonomy works like a type of social network which allows relationships among the subjects with the same interests through the use of a creative, collaborative and personalized way of content organization. Regarding the current trends of studies in the field of Librarianship and Information Science, folksonomy has functioned as a tool to assist the approaches that take into account the users and context of use of information in documentary languages.